Nirman : a skill-building initiative for semi-skilled workers in informal sector - Abhishek; Richa, Saxena (London : SAGE Publications Ltd, 2017)
SAATH is among the most respected NGOs of India catering to the needs of slum-dwellers by training them in different livelihood programs. About one and half years ago, the NGO launched Nirman program to train the workers of construction sector. After initial experimentation with processes, the Executive Director of SAATH, now plans to scale up the program. This case highlights the strengths of Nirman program and shows the impact on beneficiaries. It presents the dilemma for an organization in NGO sector to design the impact measurement process for its training program. The case also details out the challenges in implementing the training program for workers in informal sector.
Originally published: Abhishek, & Richa, S. (2014). Nirman: A skill-building initiative for semi-skilled workers in informal sector. RJMC0032. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; SAATH; Nirman; Nonprofit organizations -- India -- Case studies; Rural poor -- India -- Social conditions -- Case studies; Rural poor -- India -- Economic conditions -- Case studies; Sustainable development -- India -- Case studies